Simulation of the work of glass furnaces with the purpose of searching for reserves and increase their efficiency - Zhdanіuk, Nataliіa; Plemiannikov, Oleksii (Technology audit and production reserves, 2024)
The object of research is the operation of a glass furnace. The work involved modeling the operation of a glass furnace by changing the technical and economic indicators of its operation in order to optimize the technological processes of manufacturing glass products, increase the energy efficiency of the process, and reduce the ecological burden on the environment. Glass furnaces are complex heat engineering units that require a large amount of energy to operate. Therefore, increasing their effectiveness is the main task of our research. In the work, computer modeling of thermal processes in the furnace was carried out, heat balances were calculated and analyzed, and the performance of the furnace was analyzed after changing and improving the technological regimes of combustion processes, glass boiling and furnace construction. Studies have shown that in order to increase the technical and economic performance of glass furnaces, it is advisable to conduct additional thermal insulation of the furnace enclosures. The thermal insulation of the vault increases the efficiency of the furnace by 2–3 %, and the thermal insulation of the remaining areas of the furnace in total allows to increase the efficiency of the heating unit up to 3 %. Such measures improve the sanitary and technical working conditions of the staff in the machine-bath shop. Studies have shown that additional heating of the air used for burning fuel significantly increases the efficiency of the furnace. Thus, an increase in air temperature by 100 °C increases the efficiency of the furnace by approximately 2.5 %. However, such a measure is possible with a corresponding increase in the volume of regenerator nozzles. A significant increase in the efficiency of the furnace was achieved when additional electric heating was installed. This allows to reduce the total energy costs, and at the same time, the introduction of every 10 % of additional electric heating increases the efficiency of the furnace by up to 3 % and improves the quality of the glass mass. Such additional heating can be recommended in the amount of 20–30 % of the total heat consumption for the operation of the furnace. The analysis of the obtained results showed a fairly good convergence of the results, which indicates the acceptable adequacy of the models. The obtained process simulation results allow choosing the optimal design and operation parameters of the glass furnace. The results of the work can be used in practice for the design of efficient glass furnaces of various purposes and performance.